NetConfer: a web application for comparative analysis of multiple biological networks (vol 18, 53, 2020) - Nagpal, Sunil; Das Baksi, Krishanu; Kuntal, Bhusan K.; Mande, Sharmila S. (BMC Biology, 2020)
An amendment to this paper has been published and can be accessed via the original article.